CONSIDERATIONS REGARDING THE CREATION OF A EUROPEAN BANKING UNION – A KEY ELEMENT IN REINFORCING THE BANKING SYSTEM - Mădălina Antoaneta RĂDOI; Alexandru OLTEANU (Challenges of the Knowledge Society)
The idea of setting up a European Banking Union, an essential element in the reinforcement of the Economic and Monetary Union (EMU), has become a concrete project and it has been outlined as such after the financial crisis started in 2007. The setting up of a Banking Union is a new project for the European Union and it comes as an answer to the financial crisis; this project has three major components: the Unique Mechanism of Surveillance (UMS), the Unique Mechanism of Resolution (UMR) and the European Deposit Guarantee Schemes. At the basis of these infrastructure elements there laid: the Single Rulebook”, the unique European regulation framework (made up of the capital requirements: “CDR/CRR IV – CRD IV Directive” and “Regulation regarding capital requirements” provided together with the standards and directions issued by the European Banking Authority “ABE”) and a set of rules established for state subsidies. The large flow of important information which exists in the matter makes it necessary for us to deal with this topic in a consistent and complex argumentation.